Thyroid Autoimmunity is a Risk Factor for Recurrent Pregnancy Loss - Sultana, Sharmin; Shamima, Mosammat Nargis; Jesmin, Sahela; Zahan, Nargis; Zahid, Md Abu; Hossain, Mohd Alamgir; Mahmuda, Shahin (TAJ: Journal of Teachers Association, 2018)
This was a hospital based case control study. The study included patients attending in outdoor and indoor Department of Obstetrics and Gynaecology of Rajshahi Medical College, Hospital since July 2014 to June 2016. The aim of this study was to determine thyroid antibodies is a risk factor for recurrent pregnancy loss. Sixty seven pregnant or non pregnant women with history of recurrent miscarriage during 1st trimester were selected as case group and another sixty seven pregnant women who reached their 12 weeks uneventfully with no history of recurrent miscarriage were selected as control group. Patients with other cause of recurrent miscarriage such as metabolic or endocrinologic disorders, genital organ anomaly, uterine fibroid were excluded from the study. Thyroid function test and thyroid antibodies (FT4, TSH and TPO-Ab) were measured for the two groups. The result of this study showed that the percentage of positive TPO-Ab in target and control group is 67.16% and 5.95% respectively. The study observed that the mean serum concentrations of FT4 in the control subject was significantly higher than the mean of the target group (p-value <0.05). The TSH concentration was increased in miscarriage women with positive antibodies compared with the concentration of TSH in the control group with positive antibodies. The conclusions are that there is a deficiency in thyroid hormones or thyroid’s functional capacity is unable to meet the extra demands of pregnancy which may be one of the causes of recurrent miscarriage. Moreover positive thyroid antibodies pregnant women can reach term and have babies when the concentration of TSH is low during the first trimester, so the risk of miscarriage could be high in positive thyroid antibodies. TAJ 2017; 30(1): 49-55